Use of generative AI in project management - Berelashvili, Giorgi; Kučera, Jan; Malcová, Dana; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
Generative Artificial Intelligence is the latest breakthrough which has had a profound effect on practically all industries. Project Management is no exception and it is one of the fields extensively utilizing generative AI daily; be it for ideation, increased efficiency or completion of repetitive tasks. The research conducted in this paper defines several use cases of Generative AI currently being utilized according to existing literature. What is more, use cases based on interviews conducted with project managers within one Czech and one Georgian organization are explored. The use cases accumulated as a result of both the literature review and interview with project managers are then compared and contrasted to provide a more holistic view and properly understand how generative AI can be utilized for project success and increased efficiency. Several of the commonly mentioned use cases are then picked and showcased as part of a small-scale experiment.
Vedoucí práce: Jan Kučera
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses